Efficacy of the Protocol for Trauma Team Activation in Taipei: A Retrospective Study - Wan-Lin Chen; Ju-Chi Ou; Shih-Yu Ko; Wen-Ching Li; Hon-Ping Ma (Emergency Medicine International)
Conclusion: The Taipei prehospital field triage guidelines are acceptable but not an ideal tool for identifying patients with major trauma, with an overtriage rate of 48.12% and an undertriage rate of 12.03%. To decrease undertriage or overtriage rates, emergency medical service providers should receive comprehensive training.